2022
DOI: 10.3390/ijms23105630
|View full text |Cite
|
Sign up to set email alerts
|

Locally Secreted Semaphorin 4D Is Engaged in Both Pathogenic Bone Resorption and Retarded Bone Regeneration in a Ligature-Induced Mouse Model of Periodontitis

Abstract: It is well known that Semaphorin 4D (Sema4D) inhibits IGF-1-mediated osteogenesis by binding with PlexinB1 expressed on osteoblasts. However, its elevated level in the gingival crevice fluid of periodontitis patients and the broader scope of its activities in the context of potential upregulation of osteoclast-mediated periodontal bone-resorption suggest the need for further investigation of this multifaceted molecule. In short, the pathophysiological role of Sema4D in periodontitis requires further study. Acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Although an excess of osteoclastogenesis will lead to an inhibited effect on osteogenesis due to Scl and Sema 4D [42,43], CTHRC1 and BMP6 were con rmed to promote osteogenic differentiation [44,45]. In this study, the conditioned medium from osteoclasts did promote osteogenic differentiation and mineralization of BMSCs.…”
Section: Discussionmentioning
confidence: 51%
“…Although an excess of osteoclastogenesis will lead to an inhibited effect on osteogenesis due to Scl and Sema 4D [42,43], CTHRC1 and BMP6 were con rmed to promote osteogenic differentiation [44,45]. In this study, the conditioned medium from osteoclasts did promote osteogenic differentiation and mineralization of BMSCs.…”
Section: Discussionmentioning
confidence: 51%
“…1). Other groups have utilized similar periodontal resolution models in mice and evaluated the extent of healing 27,28 . Using this resolution model, Wong, et al showed gains in bone levels and decreased osteoclast quantity by 1 week following ligature removal and a near complete return to baseline levels by 2 weeks after ligature removal 28 .…”
Section: Discussionmentioning
confidence: 99%
“…For the induction of periodontal disease in C57BL6/J mice (6–8 weeks old; male n = 5/group), the maxillary second molar was ligatured with 5-0 silk, following the previously published protocol [ 43 , 44 ]. An anti-vimentin monoclonal antibody (5 μg/site, clone: 3CB2, mouse IgM) or isotype control IgM mAb (5 μg/site, clone: TEPC183, mouse IgM) was locally injected into the gingival tissue of a ligature-attached site every 2 days (day 0, 2, 4 and 6).…”
Section: Methodsmentioning
confidence: 99%
“…Resected maxillae were mechanically removed and exposed to 3% hydrogen peroxide overnight to remove all soft tissue. To evaluate the periodontal bone resorption, the distances from the cement–enamel junction to the alveolar bone crest on the buccal side of each root were measured for the maxillary second molar under the microscope, following the previously published protocol [ 43 , 44 ].…”
Section: Methodsmentioning
confidence: 99%